2020
DOI: 10.14742/ajet.5919
|View full text |Cite
|
Sign up to set email alerts
|

What are the barriers to learners’ satisfaction in MOOCs and what predicts them? The role of age, intention, self-regulation, self-efficacy and motivation

Abstract: Massive open online course (MOOC) participants face diverse barriers that prevent them from feeling satisfied with participating in online courses. This study identified those barriers and their predictors. Using pre- and post-questionnaires, MOOC participants reported several characteristics and their barriers to satisfaction during the course. Exploratory factor analysis identified three kinds of barriers. The effects of participants´ age, gender, level of self-efficacy, motivation, self-regulated learning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 40 publications
2
31
0
7
Order By: Relevance
“…In terms of the relationship between NOEC and participants' OLI, the results indicated that there was a negative significance. This finding was the same as that of the study of Rabin et al ( 2020 ), in which learners who intended to complete only some parts of the course activities or who did not know how many parts of the course they intended to complete faced stronger barriers to satisfaction than those who intended to complete all of the course activities. That is, the more participants engaged in online learning, the less unsatisfied (i.e., the more satisfied) they were with their learning effectiveness.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of the relationship between NOEC and participants' OLI, the results indicated that there was a negative significance. This finding was the same as that of the study of Rabin et al ( 2020 ), in which learners who intended to complete only some parts of the course activities or who did not know how many parts of the course they intended to complete faced stronger barriers to satisfaction than those who intended to complete all of the course activities. That is, the more participants engaged in online learning, the less unsatisfied (i.e., the more satisfied) they were with their learning effectiveness.…”
Section: Discussionsupporting
confidence: 87%
“…E-learning effectiveness can be improved with the assistance of online course applicability assessment (Ren et al, 2017 ). Students usually face some difficulties at the beginning of online learning that prevent them from feeling satisfied with their participation in online courses (Rabin et al, 2020 ). For example, during online learning, the most prominent disadvantage is that immediate feedback on students' performance is seldom provided, which hinders learners' learning progress (Oyekan et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, findings from various surveys highlight the positive role of (intrinsic) motivation in participation and program completion (Littlejohn, Hood, Milligan, & Mustain, 2016;Khalil & Ebner, 2017;Watted & Barak, 2018;Shukor & Sulaiman, 2019). In contrast, those motivated by extrinsic motivations face more difficulties (Rabin, Henderikx, Yoram, & Kalz, 2020). Nevertheless, extrinsic motivations can also motivate learners, especially obtaining a certificate of successful completion (Kizilcec & Schneider, 2015;Semenova, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has indicated the relationship among students' self-efficacy, engagement, and academic achievement in different learning areas (Ghazali, Nordin, Abdullah, & Ayub, 2020). Selfefficacy has been investigated much in literature (Klassen & Usher, 2010), however, only a small number of studies exploring it in a MOOC environment (Rabin, Henderikx, Kalman, & Kalz, 2020). Therefore, the purpose of this study is threefold: a) to examine if there were any changes in the self-efficacy levels of a group of students before and after they attended a MOOC, b) to explore if self-efficacy predicted their academic performance, and c) to figure out if there was any significant difference in self-efficacy and academic performance with respect to different demographic variables.…”
Section: Introductionmentioning
confidence: 99%